2017
DOI: 10.1177/1534734617690948
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Randomized Evaluation of the Effect of Low-Level Laser Therapy on Venous Leg Ulcers

Abstract: This study aimed to determine the effect of low-level laser therapy (LLLT) on chronic venous leg ulcers (VLUs). A double-blinded prospective randomized controlled trial was conducted to compare incidence of complete wound closure, ulcer size and pain reduction in patients randomized to 24 treatments of placebo or LLLT (635 nm) over 12 weeks. Patients presented with a 6-week history of VLUs ranging in size from 5 to 20 cm. Venous origin was confirmed by Doppler ultrasound and an ankle brachial index of 0.8 or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
2
20
0
2
Order By: Relevance
“…In both groups, patients will be monitored weekly until complete repair of the ulcer or for a maximum of 16 weeks. The frequency of LLLT application for this protocol was based on previous studies of phototherapy for chronic wounds [ 12 16 ]. The duration of treatment was determined based on the average healing period of a chronic wound [ 7 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both groups, patients will be monitored weekly until complete repair of the ulcer or for a maximum of 16 weeks. The frequency of LLLT application for this protocol was based on previous studies of phototherapy for chronic wounds [ 12 16 ]. The duration of treatment was determined based on the average healing period of a chronic wound [ 7 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors of these studies note that more robust research is still needed to enable standardization of parameters and expansion of LLLT to other clinical scenarios, such as venous ulcers. Additional randomized clinical trials are particularly necessary to bridge this knowledge gap [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the heterogeneity between different conditions and irradiation methods used in different surveys is the reason for which other researches have produced opposite views -that is, that LLLT application offers no benefit to the healing process. For example, some researchers have failed to achieve a statistically significant difference in healing time, in animals or humans [48][49][50].…”
Section: Low Level Laser Therapy (Lllt) and Healing Of Tissuesmentioning
confidence: 99%
“…In addition, scientists in their clinical trials have repeatedly demonstrated positive anti-inflammatory and analgesic effects in selected disease aspects in both objective terms with the use of modern laboratory equipment – eg, pathomorphological or immunocytochemical analysis of isolated tissues 6 , 7 – and subjective terms, based on the feelings of study participants regarding the symptoms of local inflammation or pain reduction. 8 10 …”
Section: Introductionmentioning
confidence: 99%